Biosubstrates Obtained from Gellan Gum for Organic Light-Emitting Diodes - Faraco, Thales A.; De O. X. Silva, Hálice; Da S. Barud, Hernane; De C. Ribeiro, Tais; Maciel, Indhira O.; Quirino, Welber G.; Fragneaud, Benjamin; Cremona, Marco; Pandoli, Omar Ginoble; Legnani, Cristiano [UNESP] (American Chemical Society (ACS), 2021)
Nowadays, flexible organic electronics are under intense investigation for environmentally friendly and biocompatible applications. One of the main components of electronic devices is the substrate, which gives support for building devices. There is great interest in the scientific community for the development of biocompatible and biodegradable substrates for the manufacture of these kinds of devices, aiming at technological and medical applications. In this work, we produced a flexible and transparent biosubstrate based on a gellan gum polymer by a solvent casting method to manufacture flexible organic light-emitting diodes (FOLEDs). The gellan substrate exhibited optical transparency of about 78% at 550 nm and 80% at 900 nm. In addition, the optimized indium tin oxide (ITO)/SiO2-coated gellan substrate exhibited a resistivity of 2.8 × 10-4 ω·cm and a sheet resistance of 11.2 ω/sq. These values are better or equal to those found in the literature for similar biosubstrates. Finally, the fabricated FOLEDs exhibited a maximum luminance of about 2327 cd/m2 and the current efficiency reached a maximum value of 2.9 cd/A. These characteristics reveal that this biosubstrate has interesting potential for applications in flexible green electronics, mainly due to its biocompatible properties and the results obtained by the developed FOLEDs.
Keywords: biopolymer; biosubstrate; gellan gum; OLED; organic light-emitting diode